Design and Energy-Economic Evaluation of a Pellet-Solar Heating System for Single-Family Houses using DIN EN 12831 in Wagete-Papua - Agustinus Giai; Ruben Mickael Kaiway; Joni Joni; Samuel Siregar (Universitas Islam Raden Rahmat, Malang, 2026)
This study presents the design and thermal analysis of a heating and ventilation system for a residential single-family house located in Wagete, Kabupaten Deiyai, Provinsi Papua Tengah, Indonesia, using the calculation procedures specified in DIN EN 12831. The design heating load was calculated to be 6,560 W, comprising transmission heat losses of 4,232 W, ventilation losses of 1,097 W, and an additional reheating capacity of 1,231 W. A pellet boiler (ETA Pellets Unit 7, 2.3–7.7 kW) combined with a flat-plate solar thermal system (4 collectors, total absorber area 9.4 m²) was selected as the heat generation system. Underfloor heating was designed for all rooms using wet-screed pipe systems (Variotherm, 16 mm aluminum composite pipes), supplemented by wall-mounted radiators in the bathroom (248 W) and shower (38 W). The annual heat demand was determined to be 17,756 kWh/a, with the solar system contributing 4,935 kWh/a (27.8%). Annual CO₂ emissions were estimated at 4,283 kg/a. The system complies with all requirements of the Energieeinsparverordnung (EnEV, 2014) and the Erneuerbare-Energien-Wärmegesetz (EEWärmeG, 2014), with a specific transmission heat loss of H'T = 0.29 W/(m²·K), well below the 0.4 W/(m²·K) limit. The methodology presented here provides a systematic, replicable framework for residential building energy system design in temperate climates, with direct relevance for energy system planning in remote highland communities in Papua Tengah, Indonesia.